URGENSI SERTIFIKASI SYARIAH BAGI NOTARIS DALAM PEMBUATAN AKTA AKAD PEMBIAYAAN DI BANK SYARIAH (Mimbar Keadilan, 2022)
In relation to business contracts in Islamic banks, the function of an authentic deed made by a Notary is as evidence that becomes the legal basis for both parties in transactions. The problem is the making of an authentic deed of financing contract that has not been implemented based on sharia principles in a kaffah manner. Therefore, this study aims to analyze the urgency of Sharia Certification for Notaries in Making Deeds of Financing Contracts at Islamic Banks. The type of research used is normative legal research with a literature study method. The approach used is the approach to legislation (statute approach) relating to the provisions of the competence requirements of the notary sharia field in making the deed of financing agreement in Islamic banks. In conclusion, the results obtained are that there are no strict and detailed laws and regulations regarding the existence of a sharia notary, even though in terms of the object, all business agreement practices in sharia banks have statutory regulations. This has an impact on the existence of a sharia notary which is still unclear. As for sharia certification training for Notaries, it is only limited to the policies of each Islamic bank management, so ensuring sharia compliance for Notaries is still a weakness and homework for Islamic banks.